Whose "Storm and Stress" Is It? Parent and Child Reports of Personality Development in the Transition to Early Adolescence. Issue 3 (23rd March 2016) - Göllner, Richard; Roberts, Brent W.; Damian, Rodica I.; Lüdtke, Oliver; Jonkmann, Kathrin; Trautwein, Ulrich
Abstract: The present study investigated Big Five personality trait development in the transition to early adolescence (from the fifth to eighth grade). Personality traits were assessed in 2, 761 (47% female) students over a 3‐year period of time. Youths' self‐reports and parent ratings were used to test for cross‐informant agreement. Acquiescent responding and measurement invariance were established with latent variable modeling. Growth curve models revealed three main findings: (a) Normative mean‐level changes occurred for youths' self‐report data and parent ratings with modest effects in both cases. (b) Agreeableness and Openness decreased for self‐reports and parent ratings, whereas data source differences were found for Conscientiousness (decreased for self‐reports and remained stable for parent ratings), Extraversion (increased for self‐reports and decreased for parent ratings), and Neuroticism (remained stable for self‐reports and decreased for parent ratings). (c) Girls showed a more mature personality overall (self‐reports and parent ratings revealed higher levels of Agreeableness, Conscientiousness, and Openness) and became more extraverted in the middle of adolescence (self‐reports). Personality changes modestly during early adolescence whereby change does not occur in the direction of maturation, and substantial differences exist between parent ratings and self‐reports.